THE RELATIONSHIP OF THE LEVEL OF PERSONAL HYGIENE KNOWLEDGE WITH THE INCIDENCE OF PITYRIASIS VERSICOLOR IN GRADUATE MEDICAL STUDENTS OF THE FACULTY OF MEDICINE, UDAYANA UNIVERSITY, CLASS OF 2022 - Kewatiting, Agnes Susanti; Darmaputra, I Gusti Nyoman; Indira, I Gusti Ayu Agung Elis; Winaya, Ketut Kwartantaya (E-Jurnal Medika Udayana, 2024)
Personal hygiene of the skin is the most important mechanism for minimizing the transmission of infections, one of which is fungal infections. The disease that most often occurs due to fungal infections is Pityriasis versicolor. This disease is caused by several factors, one of which is poor personal hygiene. This study aims to determine the relationship between the level of personal hygiene knowledge and the level of knowledge of Pityriasis versicolor with the incidence of Pityriasis versicolor in students of the Undergraduate Medical Study Program, Faculty of Medicine, Udayana University, class of 2022. This research is an observational analytical study with a cross-sectional approach. The method used is probability sampling with a simple random sampling technique. The total research sample was 170 people, of which 15 people (8.8%) had a history of Pityriasis versicolor. A total of 157 people (92.4%) had good knowledge about personal hygiene and 152 people (89.4%) had good knowledge about Pityriasis versicolor. The results of Fisher's exact test related to the relationship between the level of knowledge of personal hygiene and the level of knowledge of Pityriasis versicolor with the incidence of Pityriasis versicolor, namely p value > 0.05. This shows that there is no significant relationship between the level of knowledge of personal hygiene and the level of knowledge of Pityriasis versicolor and the incidence of Pityriasis versicolor in students of the Undergraduate Medical Study Program, Faculty of Medicine, Udayana University class of 2022. Keywords: Knowledge, Personal hygiene, Pityriasis versicolor